Penerapan Pola Pengasuhan Otoriter dalam Pengembangan Kecerdasan Sosial Anak - Sekar Anggini, Dyah Ayu; Martini; Nur Hidayaht, Achmad (Universitas Negeri Jakarta, 2023)
Parents have the right to raise children. It was found that several parents applied authoritarian parenting to develop children's social intelligence. This study aims to determine whether the application of authoritarian parenting by parents to their children can develop social intelligence. The method used is qualitative. The research was conducted in April-May, at SMP Negeri 92 Jakarta to be precise, with the research subjects consisting of six key informants and four key informants. From this study, it was found that the authoritarian parenting style adopted by parents came from internal factors (parental personality, parenting beliefs, parents' age, and parents' gender) and external factors (parents' education, socioeconomic status, and environment). Not all children who grow from authoritarian parenting have good social intelligence. Because two out of four students actually withdraw from the environment that requires them to interact. For parents who believe that applying authoritarian parenting can develop children's social intelligence, they need to pay attention to several things, such as increasing knowledge by participating in parenting training, providing fair care for each child, and living in a good social environment. In addition, the application of authoritarian parenting by parents with the aim of developing children's social intelligence should be reconsidered because there are several things that need attention, such as the child's mental condition.